Collaborating to co-produce strategies for delivering adolescent sexual and reproductive health interventions: processes and experiences from an implementation research project in Nigeria. (6th November 2020) - Mbachu, Chinyere Ojiugo; Clara Agu, Ifunanya; Onwujekwe, Obinna
Abstract: Implementation science embraces collaboration between academic researchers and key stakeholders/implementers for the dual purpose of capacity building and context-adaptation. Co-production ensures that knowledge created with inputs from various groups of stakeholders is more reflective of local contexts. This paper highlights the experiences of academic researchers and non-academic implementers in collaborating to design implementation strategies for improving access to sexual and reproductive information and services for adolescents. Data were collected through primary and secondary sources. Detailed review of project documents such as minutes of research meetings, reports of workshops and outputs of group work activities enabled detailed description of the processes and steps of co-designing implementation strategies. Information on experiences and perspectives of benefits of the collaborative were collected through in-depth interviews of non-academic partners and focus group discussion with academic researchers. Narrative synthesis was done for information extracted through document review. Thematic analysis of qualitative interviews was done. The process of designing implementation strategies happened in three chronological steps of setting up the collaborative, selecting intervention areas and convening partners' meetings to design strategies. Specific activities include stakeholder engagement, situation analysis, selection of intervention areas, designing the implementation strategies and pre-testing implementation tools. The process of analysing and selecting collaborators was iterative, and facilitated by having an 'insider' key informant. Working with key stakeholders enabled knowledge sharing and exchange among partners. Information sharing within the collaborative facilitated shifting of mindsets about adolescent sexual and reproductive health, and contextual adaptation of names and labels given to strategies. Co-producing implementation strategies with non-academic implementers enabled stakeholder ownership of implementation strategies and set the scene for their adoption in implementation settings. Some challenges of co-production of knowledge are that it is time consuming; involves several iterations that may influence coherence of strategies; involves multiple interests and priorities and poses a threat to fidelity.